ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN MORNING SICKNESS DI KLINIK ROHUL SEHAT DESA RAMBAH - Yuyun Bewelli Fahmi; Herma Yesti; Rina Julianti (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Pregnancy is an event that is very meaningful and eagerly awaited by every family, especially newly married couples. But sometimes the changes that occur at a time like this can cause physiological stress for the mother-to-be. The effect of pregnancy for each woman is different. In the first trimester, nausea and vomiting are common. Usually this is experienced in the morning or when smelling certain odors. This feeling of nausea is often called morning sickness. To comprehensively carry out midwifery care for antepartum in the first trimester with morning sickness at the Rohul Sehat Clinic, Rambah Village, using 7 steps of Varney management. This study uses an observational descriptive research method with a case study approach. Data collection techniques by means of interviews, physical examination and observation. After doing midwifery care with morning sickness which took place gradually with health education within 1 week has been resolved. It is hoped that it can provide more complete information to antepartum in the first trimester with morning sickness.